Nigerian Supreme Council for Islamic Affairs and the Quest for Unity of Muslim Ummah in Nigeria - Ibrahim Suberu (Research Synergy Foundation, 2022)
Abstract The emergence of Islamic organizations during the colonial era caused disunity among the Muslim Ummah in Nigeria. The quest to coordinate the affairs of these organizations and to unite the Muslim Ummah nationally under one umbrella led to the establishment of the Nigerian Supreme Council for Islamic Affairs (NSCIA) in 1973. This study, therefore, examines the role of NSCIA in addressing the challenges of disunity confronting the Muslim Ummah in Nigeria. Data were collected from oral interviews, questionnaires and secondary sources. A multidisciplinary approach was adopted using a combination of historical, phenomenological and sociological methods of data analysis. The theoretical framework is built on the theory of Asabiyyah by Ibn Khaldun and the theory of structural functionalism. The study discovered that the need to protect Islamic faith from colonial influence gave rise to the emergence of Islamic organizations in Nigeria. It is also discovered that Nigerian Muslims are divided along ethnic, regional and organizational lines. The study shows that despite the establishment of NSCIA in 1973, to foster unity, there are still issues bothering on disunity among the Muslim Ummah in Nigeria. Perpetuation and nothernization of the council's leadership is discovered to be a factor responsible for the inefficiency of the Council to unite the Ummah. This work recommends a review of the constitution of NSCIA for effectiveness. It also suggests rotation of its headship and that serious effort should be made by the Council at cultivating the spirit of unity among Muslims Ummah.